Psychometric properties and age- and gender-specific normative values of the Patient Health Questionnaire-4 among older adults aged 60 years and above - Nikolay Dimitrov; Elmar Brähler; Andreas Hinz; Bjarne Schmalbach; Jörg M. Fegert; Markus Zenger (BMC Geriatrics, 2026)
Abstract Background Mental health problems in older adults are often underrecognized despite their substantial impact on health and well-being. Brief, valid screening tools with age-specific normative data are needed for this growing population. This study examined the psychometric properties of the Patient Health Questionnaire-4 (PHQ-4) and established age- and gender-specific normative values for adults aged 60 years and older in Germany. Methods Data were drawn from four nationally representative face-to-face household surveys conducted in Germany between 2021 and 2024. Four of the total 3,212 participants were excluded due to missing PHQ-4 responses, resulting in a final sample of N = 3,208. The psychometric properties of the Generalized Anxiety Disorder-2 (GAD-2), the Patient Health Questionnaire-2 (PHQ-2), and the Patient Health Questionnaire-4 (PHQ-4) were evaluated. Results The PHQ-4 showed excellent internal consistency. The correlated two-factor model, distinguishing depression and anxiety symptoms, demonstrated excellent fit. Measurement invariance was supported across gender and age groups. Women reported higher overall psychological distress than men, mainly due to higher anxiety symptoms, and PHQ-4 scores were highest in the oldest age group. Convergent validity was supported by moderate to strong negative correlations with quality of life, resilience, sense of coherence, and well-being. Age- and gender-specific normative values were provided for the PHQ-2, GAD-2, and PHQ-4. Conclusions The PHQ-4 is a reliable and valid ultra-brief screening instrument for psychological distress. The age- and gender-specific normative values provided here may improve score interpretation for community-dwelling older adults in Germany and help identify individuals who may require further clinical assessment.